EFFECT OF POT DIAMETER AND FERTILIZATION WITH A SOLUTION OF ROCK DOVE MANURE ON GROWTH AND FLOWERING OF Pericallis X hybrida - A. O. Al - Atrakchii (Mesopotamia Journal of Agriculture)
This study was carried out in the college of Agriculture, Duhok University / Sumail to study the effect of Pot diameter, Organic fertilizer as solution of Rock Dove manure on growth and flowering of Pericallis X hybrida. From results of these experiments, the following conclusions may be draw: Potting plants in 20 cm diameter pots gave significantly best results for leaves number 9.01 leaf/plant, amount of chlorophyll content 69.47 mg/gm fresh weight, inflorescence height 18.49 cm and inflorescence number 41.00 inflorescence/plant. Plants manured with 10 gm/ pot/ week Rock Dove manure gave significantly better character for leaves number 9.09 leaf/ plant, amount of chlorophyll 70.28 mg/ gm fresh weight, dry weight of vegetative growth 3.26 gm/ plant, inflorescence height 18.11 cm, seed production 0.151 gm/ plant, and leaf content of NPK. But these treatments caused significantly decreasing in flowering duration. In conclusion, using 20 cm pot with addition of 10 gm/ pot/ week Rock Dove manure gave the best results for almost all characters studied.